2017
DOI: 10.1111/gcb.13885
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa agroforestry is less resilient to sub‐optimal and extreme climate than cocoa in full sun

Abstract: Cocoa agroforestry is perceived as potential adaptation strategy to sub-optimal or adverse environmental conditions such as drought. We tested this strategy over wet, dry and extremely dry periods comparing cocoa in full sun with agroforestry systems:shaded by (i) a leguminous tree species, Albizia ferruginea and (ii) Antiaris toxicaria, the most common shade tree species in the region. We monitored micro-climate, sap flux density, throughfall, and soil water content from November 2014 to March 2016 at the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 44 publications
(70 reference statements)
5
65
0
2
Order By: Relevance
“…Daily maximum temperatures much higher than the maximum monthly temperature have been reported. For example, daily maximum temperatures between 35°C and 40°C and as high as 44°C have been reported in regions of Ghana (Asare et al 2017;Abdulai et al 2018a). The monthly average maximum and minimum temperatures, which are often quoted, do not necessarily reflect absolute extremes of the temperature experienced.…”
Section: Temperature and Vapour Pressure Deficitmentioning
confidence: 99%
“…Daily maximum temperatures much higher than the maximum monthly temperature have been reported. For example, daily maximum temperatures between 35°C and 40°C and as high as 44°C have been reported in regions of Ghana (Asare et al 2017;Abdulai et al 2018a). The monthly average maximum and minimum temperatures, which are often quoted, do not necessarily reflect absolute extremes of the temperature experienced.…”
Section: Temperature and Vapour Pressure Deficitmentioning
confidence: 99%
“…Further studies estimate that cocoa production accounted for 57% of agriculture-driven deforestation in Sub-Saharan Africa from 2000 to 2013, and cocoa witnessed the highest expansion rate as compared with other exportoriented crops (Ordway et al, 2017). 3 In terms of underlying drivers of deforestation (Geist & Lambin, 2002), cocoa from West Africa is a cash crop destined almost exclusively for export markets (domestic consumption of chocolate in West Africa is minimal), explaining how deforestation is partly attributed to increasing global demand for cocoa and chocolate (Abdulai et al, 2018;Li & Mo, 2016).…”
Section: Background To Cocoa Production and The Birth Of Zero Deformentioning
confidence: 99%
“…Cocoa from this region is grown primarily on small, family-owned farms; the West African cocoa belt comprises about 2 million smallholders who depend on cocoa sales for food and income security (Kroeger, Bakhtary, et al, 2017;Schroth et al, 2016). A high proportion of these cocoa farmers are suffering from severe poverty, defined as per capita income of less than USD 1.90 per day (Abdulai et al, 2018). Poverty is often attributed to low productivity of cocoa farms.…”
Section: Background To Cocoa Production and The Birth Of Zero Deformentioning
confidence: 99%
“…Tree growth sensitivity to drought may be substantial in West African semi-arid zones, where water availability is one of the most limiting factors of plant growth, e.g., [11], and where extreme drought events are projected to become more frequent [12][13][14]. In this region, extreme drought events are associated with extended dry spells, low air humidity, high atmospheric evaporative demand, and high air temperatures [15], potentially increasing water stress in trees [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Abdulai et al [14] revealed drought vulnerability in a cocoa-based system in the forest-savanna transition zones of West Africa, despite the availability of subsoil water below a depth of 75 cm. This observation suggests that drought vulnerability may be related to trees' ability to develop sufficiently deep root systems [21].…”
Section: Introductionmentioning
confidence: 99%